2017
DOI: 10.1007/s00401-017-1745-3
|View full text |Cite
|
Sign up to set email alerts
|

Nogo-A antibodies enhance axonal repair and remyelination in neuro-inflammatory and demyelinating pathology

Abstract: Two hallmarks of chronic multiple sclerosis lesions are the absence of significant spontaneous remyelination and primary as well as secondary neurodegeneration. Both characteristics may be influenced by the presence of inhibitory factors preventing myelin and neuronal repair. We investigated the potential of antibodies against Nogo-A, a well-known inhibitory protein for neuronal growth and plasticity, to enhance neuronal regeneration and remyelination in two animal models of multiple sclerosis. We induced a ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 74 publications
2
26
0
Order By: Relevance
“…Studying spinal cord injury and stroke in animal models, it was shown that the neutralization of Nogo-A with antibodies facilitates axonal growth and functional recovery [8,81]. Using the MS mouse model EAE, blocking Nogo-A receptors ameliorated the disease course, boosted functional recovery, and increased axonal sprouting and remyelination [28,30]. Antibodies are thought to neutralize inhibitory effects of Nogo-A and thus to activate axonal and myelin regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Studying spinal cord injury and stroke in animal models, it was shown that the neutralization of Nogo-A with antibodies facilitates axonal growth and functional recovery [8,81]. Using the MS mouse model EAE, blocking Nogo-A receptors ameliorated the disease course, boosted functional recovery, and increased axonal sprouting and remyelination [28,30]. Antibodies are thought to neutralize inhibitory effects of Nogo-A and thus to activate axonal and myelin regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…We thus assessed whether myelin-axons were able to maintain the positive correlation between axonal mitochondria diameter and G-ratio during de-and remyelination. The two commonly used experimental models to study demyelination and subsequent remyelination uses; cuprizone, a dietary copper-chelating agent, and lysolecithin (LPC), an intraparenchymally injected detergent [3,14,30].…”
Section: Association Between Myelin Thickness and Axonal Mitochondriamentioning
confidence: 99%
“…Although spared and regenerated axons are myelinated, the conductive function of the axons does not change 49 . Thus, many studies demonstrated SCI repair and recovered spinal cord function through the restoration of the myelin sheath 50 52 . Our team transplanted autologous activated Schwann cells into the spinal cord, and we found relatively complete restoration of the myelin sheath and improved microenvironment balance 53 , and another study demonstrated similar results when co-transplanting human umbilical cord mesenchymal stem cells and human Schwann cells 54 .…”
Section: Tissue Imbalancementioning
confidence: 99%